The origin of microcontinents in the Central Asian Orogenic Belt: Constraints from paleomagnetism and geochronology - Levashova N.M.; Meert J.G.; Gibsher A.S.; Grice W.C.; Bazhenov M.L. (My University, 2011)
The Central Asian Orogenic Belt (CAOB) is widely recognized as a locus of Asia’s main growth during the Neoproterozoic–Paleozoic, but its evolution remains controversial. The views on the most enigmatic, late Neoproterozoic to Cambrian, stages are critically dependent on the origin and subsequent kinematics of numerous microcontinents that comprise the structure of Kazakhstan, Tien Shan, Altai and Mongolia. We report new paleomagnetic data and U–Pb zircon ages from Neoproterozoic volcano-sedimentary rocks from the Lesser Karatau block in central Kazakhstan. The laser ablation U–Pb age of felsic tuff of the Kurgan Fm. is 766 ± 7 Ma. Thermal demagnetization revealed that most studied samples retained a dual-polarity pre-tilting component whose primary origin is supported by a conglomerate test. According these paleomagnetic data, the Lesser Karatau microcontinent was located at a paleolatitude of 34.2 ± 5.3◦ , N or S, at about 770 Ma. There is only one additional CAOB microcontinent, the Baydaric microcontinent in central Mongolia, for which reliable paleomagnetic data indicate a paleolatitude of 47 ± 14◦, N or S, at about 770–805 Ma
Keywords: CAOB; Geochronology; Paleomagnetism; Paleolatitude; Late Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская